CONCEPTUALIZING MARITIM-BASED DECENTRALIZATION TOWARD BETTER PUBLIC SERVICE IN THE ARCHIPELAGIC REGION - Rahayu, Restu Karlina; Damayanti, Ratnaningsih; Mahardika, Mayuko Galuh (JWP (Jurnal Wacana Politik), 2024)
The purpose of this study is to demonstrate how decentralization affects public services differently in Sumenep Regency’s mainland and island regions. Twenty-seven subdistricts make up the Sumenep Regency; nine of these are dispersed as islands, while eighteen are situated on Madura Island. The discrepancies in growth between mainland and island are caused by this geographic structure. The infrastructure, health, and education sectors are the main subjects of this study. According to this study, obstacles that impede the optimization of education in island locations include school references and far from the Education Office and the Ministry of Religion’s oversight. In the meantime, there is disparity in the number of medical professionals and healthcare facilities in the industry. Building infrastructure that complements the features of the islands and does not harm the surrounding ecosystem requires the use of appropriate technologies. Since the natural environment has a significant influence on the characteristics of islands, the decentralization proposed cannot be compared to decentralization found on the mainland. This study recommends asymmetric decentralization for island regions as a result. Asymmetric decentralization based on maritime factors refers to decentralization that is applied to regions while accounting for the unique features of islands.